"Slime stars" (Echinodermata, Asteroidea, Velatida) from the Upper Cretaceous of northern Europe. (September 2022) - Gale, Andy
Abstract: The Cretaceous record of the predominantly deep-sea velatidan starfish families Korethrasteridae and Pterasteridae is described on the basis of dissociated, but well-preserved ossicles (adambulacrals, orals) from the Cenomanian to Maastrichtian chalks of the Anglo-Paris Basin, and marginal marine deposits at Ivö Klack, Kristianstad Basin (southern Sweden). A new genus and species of korethrasterid, Furculaster cretae gen. et sp. nov., are erected, and the only known fossil occurrence of the living genus Peribolaster is recorded from Sweden. In addition, Kutscheraster ruegenensis gen. et sp. nov. is described from the lower Maastrichtian of Rügen (northeast Germany). Seven new species of Pteraster are introduced; P. turoniense, P. seafordensis, P. nudus, P. angulatus, P. cretachiton, P. kutscheri, P. paucispinus and P. balticus . Comparative ossicle morphology permits placement of some Cretaceous species in groups of extant Pteraster (i.e., P. myonotus Group, P. temnochiton Group, P. tesselatus Group and P. pulvillus Group). It is argued that these groups had already evolved by the Late Cretaceous, providing evidence for an ancient origin of this deep-sea group.